2019
DOI: 10.2188/jea.je20180007
|View full text |Cite|
|
Sign up to set email alerts
|

Cholangiocarcinoma Trends, Incidence, and Relative Survival in Khon Kaen, Thailand From 1989 Through 2013: A Population-Based Cancer Registry Study

Abstract: Background: Cholangiocarcinoma (CCA) is a common malignancy in northeastern Thailand. Over the last 4 decades, several policies have been implemented for its prevention, but there has been no update on the trends and relative survival (RS). Our aim was (a) to perform a statistical assessment of the incidence trends of CCA and project future trends, and (b) to estimate relative survival. Methods: All cases of CCA diagnosed from 1989 through 2013 were abstracted from the Khon Kaen Cancer Registry (KKCR).A jointp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 10 publications
3
36
1
2
Order By: Relevance
“…The respective, overall, ASR of CCA among males vs. females was 44.3 per 100,000 (95% CI: 38.9 to 49.7) vs. 17.6 (95% CI: 14.5 to 20.7). Among males vs. females, the respective incidence from 1990 to 2009 had been significantly decreasing by -0.7% per year (Annual Percent Change, APC: -0.7%, 95%CI: -2.1% to +0.8%) vs. -0.4% per year (APC: -0.4%, 95% CI: -2.1% to +1.4%) [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The respective, overall, ASR of CCA among males vs. females was 44.3 per 100,000 (95% CI: 38.9 to 49.7) vs. 17.6 (95% CI: 14.5 to 20.7). Among males vs. females, the respective incidence from 1990 to 2009 had been significantly decreasing by -0.7% per year (Annual Percent Change, APC: -0.7%, 95%CI: -2.1% to +0.8%) vs. -0.4% per year (APC: -0.4%, 95% CI: -2.1% to +1.4%) [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CCA is now projected to stabilize by 2025. Notwithstanding this decline, the survival of patients with CCA remains poor [ 18 ]. A previous study referenced data between 1989 and 2013; whereas for the current study, we expanded the date range to between 1989 and 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Cholangiocarcinoma (CCA) is the most common cancer in the Northeast Thailand, especially in Khon Kaen region, although the global incidence of CCA is low (1,2). CCA is a malignant transformation of bile duct epithelium and can be anatomically classified into intrahepatic and extrahepatic types (3).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been confirmed that men have a higher odds ratio than women [ 13 ]. Surgical resection is the only potentially curative clinical therapy and results in a five-year overall survival rate between 15–40% [ 14 , 15 , 16 , 17 , 18 ]. More than two-thirds of patients relapse after resection.…”
Section: Introduction To Ccamentioning
confidence: 99%